Hepatitis C infection in non‐treatment‐seeking heroin users: The burden of cocaine injection. (6th June 2013) - Roux, P.; Fugon, L.; Jones, J.D.; Comer, S.D.
<x xml:space="preserve">Abstract</x> Background and Objectives In heroin dependent individuals, the HIV epidemic has been controlled in countries where access to opioid maintenance treatment (OMT) and needle exchange programs (NEP) have been implemented. However, despite similar routes of contamination for both viruses, the prevalence of hepatitis C (HCV) infection remains high in drug users. The objective of this analysis was to identify the prevalence of HCV and the correlates of being HCV‐positive in a sample of out‐of‐treatment heroin‐dependent individuals. Methods Data were collected from five inpatient studies (n = 120 participants) conducted at the New York State Psychiatric Institute. A logistic regression was used to identify correlates of being HCV‐positive at baseline. Results Among the 120 heroin‐dependent volunteers, 42 were HCV‐positive. Participants who had heavier alcohol use, a longer duration of heroin use, or who reported using heroin by injection were more likely to be HCV‐positive. Interestingly, participants who had injected cocaine during the previous month had a ninefold greater risk of being HCV‐positive compared to non‐cocaine users and those who used cocaine by a non‐injecting route. Conclusions and Scientific Significance These findings confirm the risk of being HCV‐infected through intravenous drug use, especially with cocaine use. These results underscore the importance of rethinking interventions to prevent HCV infection with combined strategies using pharmacological approaches for cocaine dependence and tailored prevention for cocaine users. (Am J Addict 2013;22:613–618)